DETERMINAÇÃO DE ELEMENTOS DO GRUPO DA PLATINA E OURO POR ATIVAÇÃO COM NÊUTRONS APÓS FIRE ASSAY COM SULFETO DE NÍQUEL - Jorge, A. P. S.; Enzweiller, J.; Figueiredo, A. M. G. (Geochimica Brasiliensis, 2011)